PARA ALÉM DO DUALISMO NATUREZA/CULTURA: FICÇÕES DO CORPO FEMININO - Schmidt, Rita Terezinha (Organon, 2012)
this text probes into the legacy of a central dualism of western culture – nature vs. culture – to examine how the tropo of the “natural woman” constructed in the modern period bears upon the narrative logics of two representative European novels of the XIX century: Gustave Flaubert’s Madame Bovary and Leon Tolstoi’s Ana Karenina. Then, it focuses on some scenes of Kate Chopin´s The awakening and Virgínia Woolf`s To the lighthouse to show to what extent the representation of the female characters’ experience of corporeality des-figure the dualisms upon which traditional cultural gender norms are predicated and, therefore, subvert the inscription of the body as the locus of the reproduction of femininity.